2020
DOI: 10.3389/fbioe.2020.00030
|View full text |Cite
|
Sign up to set email alerts
|

Omics Analysis Reveals the Mechanism of Enhanced Recombinant Protein Production Under Simulated Microgravity

Abstract: Simulated microgravity (SMG) is regarded as a suitable environment to produce recombinant proteins. This study showed that β-glucuronidase expressing Escherichia coli had higher productivity of recombinant protein and higher plasmid copy number under SMG compared with the normal gravity condition. The cellular changes were analyzed at both transcriptomic and proteomic levels. The upregulation of a group of ribosome/RNA polymerase genes and a cluster of genes involving energy metabolism at transcriptomic level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…A recent research revealed the mechanism causing enhanced heterologous β-glucuronidase production in E. coli under simulated microgravity by multi-omics. Its transcriptome and proteomic analysis demonstrated that ribosome function and carbon metabolism were the two main points affecting the differential expression genes response to microgravity (Huangfu et al, 2020). As discussed above, hypoxia conditions can benefit recombinant protein production in yeasts.…”
Section: Omics Techniques Drive the Stress-responsive Research For Construction Of Efficient Microbial Cell Factorymentioning
confidence: 98%
See 2 more Smart Citations
“…A recent research revealed the mechanism causing enhanced heterologous β-glucuronidase production in E. coli under simulated microgravity by multi-omics. Its transcriptome and proteomic analysis demonstrated that ribosome function and carbon metabolism were the two main points affecting the differential expression genes response to microgravity (Huangfu et al, 2020). As discussed above, hypoxia conditions can benefit recombinant protein production in yeasts.…”
Section: Omics Techniques Drive the Stress-responsive Research For Construction Of Efficient Microbial Cell Factorymentioning
confidence: 98%
“…Some researchers have proved that the microgravity condition is beneficial for microbial growth and their capacities to express recombinant proteins (Huang et al, 2012). Because it is difficult to attain the actual microgravity conditions in spaceflight due to the high cost and long duration of spaceflight, The specialized ground-based bioreactors were designed to simulate the weightlessness condition which was characterized by low sedimentation, low shear stress, and low turbulence (Huangfu et al, 2020). To achieve this, the equipment employed for providing microgravity should permit cell growth in suspension and minimize the fluid shear levels encountered by cells.…”
Section: Microgravitymentioning
confidence: 99%
See 1 more Smart Citation
“…A much better picture of cellular dynamics has emerged by transcriptomic profiling of post induction cultures [4,9,[12][13][14]. These have been combined with proteomic and metabolomics studies to show that increased acetate production, growth retardation, increased demand for maintenance energy, the down-regulation of amino acid biosynthesis, poorer substrate uptake and change in the pattern of oxygen utilization are all effects of cellular reprogramming due to stress [15][16][17][18][19]. This reprogramming works to reduce the rate of protein synthesis and hence many researchers have supplemented the expression of key down-regulated genes such as those involved in ATP synthesis, energy generation, substrate uptake and obtained significant increase in productivity [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A much better picture of cellular dynamics has emerged by transcriptomic pro ling of post induction cultures [4,9,[12][13][14]. These have been combined with proteomic and metabolomics studies to show that increased acetate production, growth retardation, increased demand for maintenance energy, the down-regulation of amino acid biosynthesis, poorer substrate uptake and change in the pattern of oxygen utilization are all effects of cellular reprogramming due to stress [15][16][17][18][19]. This reprogramming works to reduce the rate of protein synthesis and hence many researchers have supplemented the expression of key down-regulated genes such as those involved in ATP synthesis, energy generation, substrate uptake and obtained signi cant increase in productivity [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%